2018
DOI: 10.1021/acs.energyfuels.8b01397
|View full text |Cite
|
Sign up to set email alerts
|

Methane Adsorption Characteristics and Adsorption Model Applicability of Tectonically Deformed Coals in the Huaibei Coalfield

Abstract: Based on methane isothermal adsorption experiments, the supercritical methane adsorption characteristics of middle-rank tectonically deformed coals (TDCs) screened from the Huaibei coalfield were analyzed. The applicability of different adsorption models to different kinds of TDCs was discussed using the standard deviation method, and the mechanism of methane adsorption in TDCs was explored. The following results were obtained. First, the experimental maximum adsorption capacity of TDCs increases gradually wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The greater the burial depth of the coal seam, the larger the in-situ stress and the greater the distance of gas escape, which is also conducive to gas sealing. The greater the thickness of the coal seam, the more conducive it is to gas preservation (Lu et al 2018b;Kang et al 2020;Li et al 2020b). However, some studies have shown that the depth effect is no longer obvious when the depth of coal seam exceeds the critical point of 800-900 m (Li et al 2020a).…”
Section: Understanding Of Coal Seam Gas Occurrence Characteristicsmentioning
confidence: 99%
“…The greater the burial depth of the coal seam, the larger the in-situ stress and the greater the distance of gas escape, which is also conducive to gas sealing. The greater the thickness of the coal seam, the more conducive it is to gas preservation (Lu et al 2018b;Kang et al 2020;Li et al 2020b). However, some studies have shown that the depth effect is no longer obvious when the depth of coal seam exceeds the critical point of 800-900 m (Li et al 2020a).…”
Section: Understanding Of Coal Seam Gas Occurrence Characteristicsmentioning
confidence: 99%
“…Therefore, it is of great theoretical and practical significance to carry out micro‐nano pore evaluation of tight reservoirs. In recent decades, the main experiments that can be used to quantitatively determine pore structure are capillary pressure curve method, binary image computer analysis (PIA), displacement method, and the pore three‐dimensional space shape computer reconstruction method . As classical high‐precision experiments for pore structure analysis, mercury intrusion analysis has been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the main experiments that can be used to quantitatively determine pore structure are capillary pressure curve method, binary image computer analysis (PIA), displacement method, and the pore three-dimensional space shape computer reconstruction method. [1][2][3][4][5][6][7][8][9][10][11] As classical high-precision experiments for pore structure analysis, mercury intrusion analysis has been widely used. However, it has many defects, such as core damage, environmental pollution and high cost, so it is difficult to carry out on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is a stress-sensitive porous medium. Tectonically deformed coal (TDC) with various structures will form under different stress–strain environments. TDCs occur in almost all major coal-producing countries in the world. TDCs develop widely in Chinese coal-bearing basins as China has experienced multistage tectonic movements . Various TDCs have different pore structures and methane adsorption characteristics, which affect the recovery of coalbed methane (CBM) and the prevention of coal and gas outburst. , For example, the brittle deformation sequence of TDCs may be the target layer for CBM recovery, and the occurrence of mylonitic coal may lead to the coal and gas outburst in the underground coalmine .…”
Section: Introductionmentioning
confidence: 99%